ESTIMATION OF COMPONENTS OF GENETIC VARIANCE IN MAIZE (ZEA MAYS L.) - KUMAR, NARENDRA; V. N. JOSHI; M. C. DAGLA (The Bioscan, 2013)
A total 256 full sib progenies (64 half sib families) of a large random mating heterozygous population of maize composite Mahidhawal were evaluated in two environments consisting of two different levels of fertility viz., (i) high N (E1) and (ii) low N (E2). The estimate of additive variance for grain yield per plant was positive and significant in E2 and pooled analysis while it was positive but non-significant in E1. This suggested additive variance is more important in determining grain yield under low N. Dominance variance for grain yield per plant was positive significant in E1, E2 and pooled analysis but higher magnitude under high N. This indicated that both additive variance and dominance variance contribute significant role in expression of total genetic variability for seed yield and other traits. Additive x environments interaction components were non-significant for all the traits In contrast, dominance x environments interaction components were positive significant for days to 50% tasseling, days to 50% silking, 100 - grain weight, grain yield per plant and stover yield per plant. Study of dominance ratio revealed that the genes responsible for expression of majority of traits including grain yield per plant showed complete dominance to over dominance.